2015
DOI: 10.1158/0008-5472.can-14-0652
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming of the ERRα and ERα Target Gene Landscape Triggers Tamoxifen Resistance in Breast Cancer

Abstract: Endocrine treatment regimens for breast cancer that target the estrogen receptor-a (ERa) are effective, but acquired resistance remains a limiting drawback. One mechanism of acquired resistance that has been hypothesized is functional substitution of the orphan receptor estrogen-related receptor-a (ERRa) for ERa.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 48 publications
4
29
0
Order By: Relevance
“…While the specific activities of the ERRs in cancer certainly extend beyond regulating energy metabolism [43,77,81,106,112,113], the findings summarized herein are in support of the view that the ERRs play a central role in coordinating oncometabolic programs which then fuel cancer cell proliferation, migration, angiogenesis and metastasis (Fig. 1).…”
Section: Discussionsupporting
confidence: 78%
“…While the specific activities of the ERRs in cancer certainly extend beyond regulating energy metabolism [43,77,81,106,112,113], the findings summarized herein are in support of the view that the ERRs play a central role in coordinating oncometabolic programs which then fuel cancer cell proliferation, migration, angiogenesis and metastasis (Fig. 1).…”
Section: Discussionsupporting
confidence: 78%
“…The EGF pathway can therefore be an alternative activator for ESR1 signaling in breast cancer and provides a molecular explanation for the endocrine therapy resistance often seen in ER+ERBB2+ breast cancers. Analysis of ESR1 and ESRRA cistromes in tamoxifen-sensitive vs -resistant breast cancer cells showed that despite regulating distinct transcriptional networks, their cistromes are reprogramed in tamoxifen-resistant breast cancer cells toward the regulation of genes functionally relevant to resistance (Thewes et al 2015). These studies show that NR binding profiles can be shifted in a contextdependent manner, resulting in altered transcriptional networks that affect disease progression and outcome.…”
Section: Reprogramming Of Nr Binding and Disease Progressionmentioning
confidence: 88%
“…Although ESRRA is associated with increased recurrence and poor outcome (Thewes et al 2015), ESRRG expression is correlated with ESR1 and ERBB4, which are markers of favorable outcome (Ariazi et al 2002). It has been suggested that ESRRA and ESRRG have opposite roles in the regulation of metabolic reprogramming of breast cancer cells (Deblois & Giguere 2013).…”
Section: Estrogen-related Receptors (Errs)mentioning
confidence: 99%
“…Although it has anti-estrogen activity, TAM is widely used to treat ER-positive breast tumors as an adjuvant therapy for early-stage hormone-sensitive breast cancer or first line therapy for metastatic hormone-sensitive breast cancer, and as many as 30% of patients can be refractory to TAM and acquire resistance to TAM along with the loss of ER-α [6, 2224]. CK-α is one of the targets of therapeutic strategies because it is a key enzyme in choline metabolism and might contribute to TAM resistance [11, 19].…”
Section: Discussionmentioning
confidence: 99%